Locus coeruleus norepinephrine activity mediates sensory-evoked awakenings from sleep - Hayat, Hanna (Sci Adv, 2020)
A defining feature of sleep is reduced responsiveness to external stimuli, but the mechanisms mediating sensory-evoked arousal remain unclear. We hypothesized that reduced locus coeruleus (LC) norepinephrine (NE) activity during sleep mediates unresponsiveness, and its action promotes sensory-evoked awakenings. We tested this using electrophysiological, behavioral, pharmacological, and optogenetic techniques alongside auditory stimulation in freely behaving rats. We found that systemic reduction in NE signaling lowered probability of sound-evoked awakenings (SEAs). The level of tonic LC activity during sleep anticipated SEAs. Optogenetic LC activation promoted arousal as evident in sleep-wake transitions, EEG desynchronization, and pupil dilation. Minimal LC excitation before sound presentation increased SEA probability. Optogenetic LC silencing using a soma-targeted anion-conducting channelrhodopsin (stGtACR2) suppressed LC spiking and constricted pupils. Brief periods of LC opto-silencing reduced the probability of SEAs. Thus, LC-NE activity determines the likelihood of sensory-evoked awakenings, and its reduction during sleep constitutes a key factor mediating behavioral unresponsiveness.